A COMPLETE PENETRATION TESTING FRAMEWORK: SIMULATING ATTACKS AND EVALUATING POST-EXPLOITATION TECHNIQUES WITH KALI LINUX AND METASPLOIT - Fahad Amin,; Nadeem Daudpota,; Dr Ajab Khan, (Spectrum of Engineering Sciences, 2025)
As cyber threats continue to grow in complexity, organizations face increasing pressure to test the real-world resilience of their information systems. This study introduces a hands-on penetration testing framework that spans all five critical phases: reconnaissance, vulnerability identification, exploitation, privilege escalation, and post-exploitation. Using Kali Linux as the core testing environment and Metasploit as the primary exploitation toolkit, we simulate both internal and external attack vectors in a virtual lab. Unlike many existing approaches that focus primarily on gaining access, this research places particular emphasis on post-exploitation tactics—including token theft, persistence, and lateral movement—to explore how attackers maintain long-term control. A custom testbed, comprising pre-configured vulnerable systems, was used to replicate realistic enterprise conditions and evaluate how post-breach actions can compromise data integrity, system availability, and administrative authority. The outcomes include detailed insights into attacker behavior after initial access and the challenges system administrators face in detection and mitigation. The study also outlines strategies for reporting, interpreting results, and reinforcing security baselines. This comprehensive framework not only guides cybersecurity professionals and ethical hackers in executing end-to-end tests but also contributes to the academic understanding of full-cycle penetration methodologies. By bridging theoretical concepts with practical application, this work supports the advancement of proactive defense strategies in a constantly evolving threat landscape.